Perinatal derivatives: How to best characterize their multimodal functions in vitro. Part C: Inflammation, angiogenesis, and wound healing - Flores, Ana I.; Pipino, Caterina; Jerman, Urška Dragin; Liarte, Sergio; Gindraux, Florelle; Kreft, Mateja Erdani; Nicolas, Francisco J.; Pandolfi, Assunta; Tratnjek, Larisa; Giebel, Bernd; Pozzobon, Michela; Silini, Antonietta R.; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Perinatal derivatives (PnD) are birth-associated tissues, such as placenta, umbilical cord, amniotic and chorionic membrane, and thereof-derived cells as well as secretomes. PnD play an increasing therapeutic role with beneficial effects on the treatment of various diseases. The aim of this review is to elucidate the modes of action of non-hematopoietic PnD on inflammation, angiogenesis and wound healing. We describe the source and type of PnD with a special focus on their effects on inflammation and immune response, on vascular function as well as on cutaneous and oral wound healing, which is a complex process that comprises hemostasis, inflammation, proliferation (including epithelialization, angiogenesis), and remodeling. We further evaluate the different in vitro assays currently used for assessing selected functional and therapeutic PnD properties. This review is a joint effort from the COST SPRINT Action (CA17116) with the intention to promote PnD into the clinics. It is part of a quadrinomial series on functional assays for validation of PnD, spanning biological functions, such as immunomodulation, anti-microbial/anti-cancer activities, anti-inflammation, wound healing, angiogenesis, and regeneration.